Some Investigations on the Anisotropy of the Chemical Etching of (h k 0) and (h h I) Silicon Plates in a NaOH 35% Solution. Part III: Determination of a Database for the Simulator Tensosim and Prediction of 2D Etching Shapes - C. R. Telliera; C. Hodebourg; T. G. Leblois (Active and Passive Electronic Components)
The simulation of 2D etching shapes such as surface profiles and out-of-roundness profiles related to various (h k 0) and (h h l) silicon plates or cross-sections is studied. The theoretical basis of the simulation is presented. The database for the simulator TENSOSIM is determined from a systematic analysis of experimental 2D etching shapes. Emphasis is placed on difficulties encountered in the determination procedure. Theoretical 2D etching shapes are compared with experimental shapes. A correlation between polar plots of the dissolution slowness and corresponding theoretical shapes is established. So we can conclude that the accuracy of the proposed database is sufficient for the simulation of 2D etching shapes.